2012
DOI: 10.1007/s11033-012-1914-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity study of some medicinal plant accessions belong to Apiaceae family based on seed storage proteins patterns

Abstract: Cumin (Cuminum cyminum L.), Fennel (Foeniculum vulgare L.) and Longleaf (Falcaria vulgaris Bernh) that all belong to Apiaceae family as medicinal plants are very important in many countries. Study of genetic diversity for medicinal plant is important for researches in future. One of the methods to evaluate plant genetic diversity and classification of them is the electrophoresis of seed storage proteins. This research was conducted in order to evaluate seed protein variability in different Iranian Cumin, Fenne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…SSR and ISSR, among all marker systems, are the most popular markers based on polymerase chain reaction. These markers (SSR and ISSR) have been used widely to analyze of the genetic diversity among different species of plants (Masoumi et al 2012). Simple sequence repeats (SSRs) are tandem repeats of 1 to 6 nucleotides in both coding and non-coding regions.…”
Section: Introductionmentioning
confidence: 99%
“…SSR and ISSR, among all marker systems, are the most popular markers based on polymerase chain reaction. These markers (SSR and ISSR) have been used widely to analyze of the genetic diversity among different species of plants (Masoumi et al 2012). Simple sequence repeats (SSRs) are tandem repeats of 1 to 6 nucleotides in both coding and non-coding regions.…”
Section: Introductionmentioning
confidence: 99%
“…The relative proportions of these storage protein fractions varied from one species to another and even between varieties of same species; however, this variation was independent from the environmental variation (MASOUMI et al, 2012). Hence, it can be concluded that the concentration of different storage proteins varies with species.…”
Section: Resultsmentioning
confidence: 90%
“…vulgaris was examined in the present study (18). Previous studies have shown that beta-caryophyllene, alpha-pinene, and limonene are compounds with antileishmanial activities (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%